Determination of yield parameters and essential oil composition in some lemon balm (Melisa officinalis L.) populations - Öner, Emel Karaca; Uzun, Arslan (Emirates Journal of Food and Agriculture, 2023)
In this research, it is aimed to determine some parameters such as seedling growth, yield and essential oil components of lemon balm (Mellissa officinalis L.) populations belong to Samsun, Ordu, Trabzon and Artvin provinces in Turkey. Some morphological parameters such as plant height, number of leaves, peduncle length, leaf length, some yield parameters such as fresh herb yield (gr/plant), drug herb yield (gr/plant) and drug leaf yield (gr/plant) and some quality parameters such as essential oil ratio (%) and essential oil components of the populations were investigated. According to the results of the research, it was determined that the plant height values between 41.36 cm and 100.41 cm, the yield of fresh herb varies between 164.34 g/plant and 481.45 g/plant and the essential oil ratio values vary between 0.19% and 0.325%. Keywords: Drog herb; Fresh herb; Beta-Caryophyllene; Caryophyllene oxide.